Gambaran Pengetahuan Komunitas Mobil di DKI Jakarta dalam Menjaga Kebersihan Selama Berkendara. - Sharren Teguh; Tri Erri Astoeti; Yohana Yusra (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Covid 19 pandemic is one of the worst pandemics in the world. Indonesia also affected with this pandemic with high mortality numbers. But with time, people must do their activity again outside their home. Car is one of transportation option in DKI Jakarta with large quantity. Many people using car but lack of understanding on how to keep clean in riding a car, as private or public vehicle. Purpose of community service (PkM) is to educate one of car community in DKI Jakarta which is White Car Community chapter Batavia which consist of various of people from many places in DKI Jakarta which owns white car. The implementation was done online on December 13, 2020. In this program before and after education, was given a questionnaire on how to keep clean in riding car to see the knowledge of the community member in keeping clean while riding a car. In result this community service increase awareness and knowledge of Covid-19 in community member of White Car Community chapter Batavia. Similar activity needed to be done because of fluctuation transmission of covid-19.